Competences and Attitudes of Internal Medicine Research Assistants Working in COVID-19 Inpatient Services About Nutrition: A Survey Study - Ceylan, Serdar; Kahyaoğlu, Zeynep; Guner Oytun, Merve; Okyar Baş, Arzu; Doğu, Burcu Balam; Cankurtaran, Mustafa; Halil, Meltem Gülhan (Acta Medica, 2022)
Objective: COVID-19 increases risk of malnutrition. With proper nutritional management, clinical outcomes are more positive but nutritional management is often overlooked. Aim of our study is to determine competences and attitudes of internal medicine research assistants working in COVID-19 services in terms of nutritional management and the factors that may affect this. Materials and Methods: A 12-question survey was applied to internal medicine research assistants worked/still working in the inpatient service and intensive care units where COVID-19 patients were followed up. Their competences and attitudes about nutrition were learned. Results: A hundred research assistants participated in the study. Ratio of those who considered their knowledge sufficient about nutrition management was 48% (n=48), enteral nutrition was 62% (n=62) and parenteral nutrition was 55% (n=55). There were 92 (92%) research assistants who thought that nutrition was a problem in COVID-19 patients, however there are only 6 (6%) research assistants who have read publications on nutritional management in COVID-19 patients. Research assistants who have performed intensive care or geriatrics rotation stated themselves more competent in nutrition (p = 0.001 & p <0.001, respectively) and who have performed geriatrics rotation thought that they have sufficient knowledge about enteral nutrition (p = 0.03). Conclusion: Research assistants who play important roles in the management of patients, find themselves highly incompetent in nutritional management, although they know that nutritional management will yield positive results on the patient’s clinical outcomes. Importance of education of research assistants about nutrition should be emphasized in order to apply nutritional support better.